Impact of weight management nutrition interventions on dietary outcomes in children and adolescents with overweight or obesity: a systematic review with meta‐analysis. Issue 1 (6th December 2020) - Duncanson, K.; Shrewsbury, V.; Burrows, T.; Chai, L. K.; Ashton, L.; Taylor, R.; Gow, M.; Ho, M.; Ells, L.; Stewart, L.; Garnett, S.; Jensen, M. E.; et al.
Abstract: Background: The impact of obesity interventions on dietary intake in children and adolescents with overweight or obesity is unclear. This systematic review aimed to investigate the impact of the dietary component of weight management interventions on the change in diet in children and adolescents with overweight or obesity. Methods: Eligible randomised controlled trials (RCTs) published between 1975 and 2020 were identified by a systematic search following Preferred Reporting Items for Systematic Reviews and Meta‐analyses (PRISMA) guidelines. Meta‐analyses of eligible study outcomes were performed using statistical software. A multilevel random effects model was used with three significant random effects fitted using restricted maximum likelihood estimation. Results: This review identified 109 RCTs, including 95 that reported at least one statistically significant dietary outcome change and 14 reporting no significant dietary change. Results from the meta‐analyses ( n  = 29 studies) indicated that, compared to control groups, intervention groups achieved significantly greater reductions in mean total energy intake at ≤6 months (−194 kcal day −1, 95% confidence interval = −275.80 to −112.90 kcal day −1, P  < 0.001) and up to 12 months (−112 kcal day −1 95% confidence interval = −218.92 to −5.83 kcal day −1 ) P  = 0.038), increases in fruit and/or vegetable intakes over 2–12 months ( n =  34, range +0.6 to +1.5 servings day −1 ) and reductions in consumption of sugar‐sweetened beverages ( n =  28, range −0.25 to −1.5 servings day −1 ) at 4–24 months follow‐up. Conclusions: Obesity interventions with a dietary component have a modest but sustained impact on reducing total energy intake and improving intakes of specific food groups in children and adolescents with overweight or obesity. High quality RCTs that are powered to detect change in diet as a primary outcome are warranted. Abstract : This systematic review analysed the impact of the dietary component of interventions on dietary intake in children and adolescents who were overweight or obese. The findings from this review indicated that interventions with a dietary component contribute to a greater reduction in total energy intake and improve intakes of specific food groups in children and adolescents with overweight or obesity.